Petrel TSM 5424 Three Dimensional Sonar for Shallow Water Coastal Hydrographic Feature Detection - Ellis, Colin (The International Hydrographic Review, 2018)
This is a charting hydrographer’s perspective on the potential for the PETREL 5424 three dimensional mine avoidance sonar to be exploited as a hydrographic sensor for shallow water 10-100 metre feature detection. It projects the advantages of three dimensional ensonification over athwartship systems and provides an overview of the success of PETREL sea trials conducted in conjunction with the Royal Australian Navy in April 1998. The paper further reports on continuing development of a hydrographic variant to the PETREL. In conclusion it proposes that PETREL can revolutionise mission efficiency and safety within the coastal hydrographic feature detection mission by allowing faster vessel speeds, wider line spacing and easier planning. The views expressed are those of the author.